2011
DOI: 10.2527/jas.2010-3301
|View full text |Cite
|
Sign up to set email alerts
|

RUMINANT NUTRITION SYMPOSIUM: Role of fermentation acid absorption in the regulation of ruminal pH12

Abstract: Highly fermentable diets are rapidly converted to organic acids [i.e., short-chain fatty acids (SCFA) and lactic acid] within the rumen. The resulting release of protons can constitute a challenge to the ruminal ecosystem and animal health. Health disturbances, resulting from acidogenic diets, are classified as subacute and acute acidosis based on the degree of ruminal pH depression. Although increased acid production is a nutritionally desired effect of increased concentrate feeding, the accumulation of proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
385
5
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(419 citation statements)
references
References 144 publications
(223 reference statements)
18
385
5
11
Order By: Relevance
“…A major objective of our study was to determine whether changes in the ruminal SCFA profile when the supply of rapidly fermentable CHO in beef cattle is altered has an effect on ruminal epithelial permeability to SCFA. Passive diffusion of protonated (HSCFA) and protein-mediated transport of anionic SCFA (SCFA − ) are thought to be the major pathways for absorption of ruminal acid (Aschenbach et al, 2011). Compared with passive diffusion, limited research has been carried out to characterize the different protein-mediated transport systems involved, and their functional relevance to pH regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A major objective of our study was to determine whether changes in the ruminal SCFA profile when the supply of rapidly fermentable CHO in beef cattle is altered has an effect on ruminal epithelial permeability to SCFA. Passive diffusion of protonated (HSCFA) and protein-mediated transport of anionic SCFA (SCFA − ) are thought to be the major pathways for absorption of ruminal acid (Aschenbach et al, 2011). Compared with passive diffusion, limited research has been carried out to characterize the different protein-mediated transport systems involved, and their functional relevance to pH regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous C flow was estimated from endogenous CP and fat flow using the C content of bacterial fat and protein according to Reichl and Baldwin (1975). Possible bicarbonate flow at the duodenum was not considered as it was assumed that all bicarbonate is converted into CO 2 in the abomasum (Aschenbach et al, 2011;Dijkstra et al, 2012). According to glucose fermentation stoichiometry, 3 mol C are used for 1 mol Ac (2 mol C for Ac, 1 mol C for CO 2 ) and for 1 mol Pr, and 6 mol C for 1 mol Bu (4 mol C for Bu, 2 mol C for CO 2 ) and for 1 mol Va.…”
Section: Calculationsmentioning
confidence: 99%
“…The reason for the lower pH of the Low group can be due to an increased DMI found in this group of cows. Because ruminal pH is a product of both fermentation and neutralization processes, with chewing activity and inherent absorption and metabolization capacity of the rumen epithelium playing a role (Aschenbach et al, 2011), these factors might also have contributed to the differences in ruminal pH among groups.…”
Section: Lipolysis In Periparturient Cowsmentioning
confidence: 99%
“…Rumen pH is routinely used as an indicator of rumen health, as pH reflects both the ruminal milieu needed for proper ruminal functioning and also indicates the fermentation output available as energy source for gluconeogenesis and milk production (Aschenbach et al, 2010 and, thus likely modulating the metabolic adaptation of the transition cow. Nevertheless, as ruminal pH is also affected by neutralisation processes (Aschenbach et al, 2011), these factors might also contribute to rumen health and metabolic adaptation of periparturient dairy cows. We have recently demonstrated that transition dairy cows show different responses of ruminal pH despite similar feeding management (Humer et al, 2015a), posing them at different risks of rumen fermentation disorders postpartum.…”
Section: Introductionmentioning
confidence: 99%